2007
DOI: 10.1186/1740-3391-5-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high correlated colour temperature office lighting on employee wellbeing and work performance

Abstract: Background: The effects of lighting on the human circadian system are well-established. The recent discovery of 'non-visual' retinal receptors has confirmed an anatomical basis for the nonimage forming, biological effects of light and has stimulated interest in the use of light to enhance wellbeing in the corporate setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
218
5
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(237 citation statements)
references
References 26 publications
11
218
5
3
Order By: Relevance
“…However, this effect was related to the time of the day and not specifically to condition daylight or electric light. Self-reported vitality could also be improved after an intervention of 17000 K lighting 35,37 . In addition, Mills et al 37 showed an effect of bright light (17000 K lighting) on fatigue and light headedness, measured by the Columbia Jet Lag Scale.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…However, this effect was related to the time of the day and not specifically to condition daylight or electric light. Self-reported vitality could also be improved after an intervention of 17000 K lighting 35,37 . In addition, Mills et al 37 showed an effect of bright light (17000 K lighting) on fatigue and light headedness, measured by the Columbia Jet Lag Scale.…”
Section: Resultsmentioning
confidence: 84%
“…An X indicates that the health outcome was investigated, it does not give any indication on the strength or significance of the correlation between that health indicator and the office light conditions References Borisuit et al 33 Münch et al 34 Viola et al 35 Linhart et al 36 Mills et al 37 Figueiro et al 38 Das 39 Kozaki et al 40 Vetter et al 41 Maleetipwan-Mattsson et al 42 Geerdinck et al 43 Viitanen et al 44 Veitch et al 15 Villa et al 45 Hedge et al 46 Jafari et al 47 Hirning et al 48 Hirnign et al 49 Xia et al…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12,13 The healthiest quarter of the workforce are shown to be happier, less prone to illness and 18 per cent more productive than the least healthy quarter. 14 Nevertheless, the health of the workforce (as a reflection of the UK population more generally) is in decline.…”
mentioning
confidence: 99%